PELAYANAN PEMANDU WISATA PADA RUMAH SINGGAH TUAN QADHI KOTA PEKANBARU - Riris "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The this research aims to find out how the Tour Guide Services at Tuan Qadhi Halfway House in Pekanbaru City. This research used qualitative descriptive method to analyze the problem. The sample in this research are 90 samples by using accidental sampling. And then the teqniques to collected data in this research are using observation, questionnaire and interview. And it was using likert scale to know the length of intervals. Based on the result of the research thas’s been done, Tour Guide Services at Tuan Qadhi Halfway House in Pekanbaru City with sub-variabeles of Good appearance, Proffesionalism, Matery of material, Fiendly, Weldressed with good conlusions. Keywords: Service, Tour Guide, The Place Tuan Qadhi Halfway House